2022
DOI: 10.3389/fphar.2022.1082797
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive assessment on the applications of oncolytic viruses for cancer immunotherapy

Abstract: The worldwide burden of cancers is increasing at a very high rate, including the aggressive and resistant forms of cancers. Certain levels of breakthrough have been achieved with the conventional treatment methods being used to treat different forms of cancers, but with some limitations. These limitations include hazardous side effects, destruction of non-tumor healthy cells that are rapidly dividing and developing, tumor resistance to anti-cancer drugs, damage to tissues and organs, and so on. However, oncoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 194 publications
0
7
0
Order By: Relevance
“…The application of oncolytic viruses is not without potential side effects on non-tumour cells ( 104 ). While oncolytic viruses are designed to selectively target and destroy cancer cells, they may inadvertently impact neighbouring healthy cells ( 105 ).…”
Section: Discussionmentioning
confidence: 99%
“…The application of oncolytic viruses is not without potential side effects on non-tumour cells ( 104 ). While oncolytic viruses are designed to selectively target and destroy cancer cells, they may inadvertently impact neighbouring healthy cells ( 105 ).…”
Section: Discussionmentioning
confidence: 99%
“… 96 Further studies have shown that T-VEC can be used in combination with other immunotherapies such as anti-PD-1 to enhance treatment response rates ( Figure 4 A). 97 , 98 , 99 , 100 …”
Section: Immunogenic Virus Approachesmentioning
confidence: 99%
“…Current and future research on OV therapies aims to address the potential for off-target virulence and toxicity and find methods to mitigate or utilize innate antiviral immune responses that can otherwise inhibit OV efficacy, allowing for systemic or repeat administration. 86 , 98 , 101 …”
Section: Immunogenic Virus Approachesmentioning
confidence: 99%
“…However, more advanced methodologies such as gene therapy, stem cell therapy (induced pluripotent stem cells, embryonic stem cells, hemopoietic stem cells, neuronal stem cells, and cancer stem cells), monoclonal antibodies, nano-based medicine, ablation (thermal ablation, cryoablation, and radiofrequency ablation), and chemodynamic and ferroptosis-based therapies, along with radiodynamic therapies, radionics, chitosan-based photodynamic therapy, targeted delivery-based therapy modalities using folic acidconjugated photo-responsive polymeric particles, oncolytic virus-based therapy, and natural antioxidant therapies, have been explored in the cancer treatment. Some of these interventions are at different stages of development, and a few are already being approved and utilized for the treatment of various cancers [7][8][9][10][11]. The anticancer properties of thioredoxin-binding protein (TXNIP) have been investigated for its application to treat cancer [12].…”
Section: Review Cancer Treatment Modalitiesmentioning
confidence: 99%